Clinical outcomes of chronic heart failure patients with unsuppressed sleep apnea by positive airway pressure therapy - Naito, Ryo; Kasai, Takatoshi; Tomita, Yasuhiro; Kasagi, Satoshi; Narui, Koji; Momomura, Shin-Ichi (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Heart failure (HF) is an advanced-stage cardiac disease associated with a high mortality rate. Previous studies have shown that sleep apnea (SA) is associated with a poor prognosis in patients with HF. The beneficial effects of PAP therapy, which effectively reduces SA in cardiovascular events, have not yet been established. However, a large-scale clinical trial reported that patients with central SA (CSA), which is not effectively suppressed by continuous positive airway pressure (CPAP), have a poor prognosis. We hypothesized that CPAP-induced unsuppressed SA is associated with negative consequences in patients with HF and SA, including obstructive SA (OSA) or CSA. Methods: This was a retrospective, observational study. Patients with symptomatic HF, defined as left ventricular ejection fraction of ≤ 50% and New York Heart Association class ≥ II; those who underwent sleep studies and were diagnosed with an SA [apnea–hypopnea index (AHI) of ≥ 15/h on overnight polysomnography]; and those treated with CPAP therapy for 1 month who underwent another sleep study with CPAP were enrolled. The patients were classified into two groups according to AHI on CPAP (suppressed group, residual AHI ≥ 15/h; and unsuppressed group, residual AHI < 15/h). The primary endpoint was a composite of all-cause death and hospitalization for HF. Results: Overall, data from 111 patients, including 27 patients with unsuppressed SA, were analyzed. The cumulative event-free survival rates were lower in the unsuppressed group during a period of 36.6 months. A multivariate Cox proportional hazard model showed that the unsuppressed group was associated with an increased risk for clinical outcomes (hazard ratio 2.83, 95% confidence interval 1.12–7.12, p = 0.028). Conclusion: Our study suggested that in patients with HF and SA including either OSA or CSA, presence of unsuppressed SA even on CPAP was associated with worse prognosis than patients with suppressed SA by CPAP.